The Effect of Prenatal Food Restriction on Brain Proteome in Appropriately Grown and Growth Restricted Male Wistar Rats - Potiris, Anastasios; Manousopoulou, Antigoni; Zouridis, Andreas; Sarli, Polyxeni-Maria; Pervanidou, Panagiota; Eliades, George; Perrea, Despina N.; Deligeoroglou, Efthymios; Garbis, Spiros D.; Eleftheriades, Makarios (Frontiers in Neuroscience, 2021)
Background Fetal growth restriction (FGR) has been associated with a higher risk of developing adverse perinatal outcomes and distinct neurodevelopmental and neurobehavioral disorders. The aim of the present study was to investigate the impact of prenatal food restriction on the brain proteome in both FGR and appropriately grown rats and to identify potential pathways connecting maternal malnutrition with altered brain development. Methods Ten time-dated pregnant Wistar rats were housed individually at their 12th day of gestation. On the 15th day of gestation, the rats were randomly divided into two groups, namely the food restricted one (n = 6) and the control group (n = 4). From days 15 to 21 the control group had unlimited access to food and the food restricted group was given half the amount of food that was on average consumed by the control group, based on measurements taken place the day before. On the 21st day of gestation, all rats delivered spontaneously and after birth all newborn pups of the food restricted group were weighed and matched as appropriately grown (non-FGR) or growth restricted (FGR) and brain tissues were immediately collected. A multiplex experiment was performed analyzing brain tissues from 4 FGR, 4 non-FGR, and 3 control male offspring. Differentially expressed proteins (DEPs) were subjected to bioinformatics analysis in order to identify over-represented processes. Results Proteomic analysis resulted in the profiling of 3,964 proteins. Gene ontology analysis of the common DEPs using DAVID (https://david.ncifcrf.gov/) showed significant enrichment for terms related to cellular morphology, learning, memory and positive regulation of NF-kappaB signaling. Ingenuity Pathway Analysis showed significant induction of inflammation in FGR pups, whereas significant induction of cell migration and cell spreading were observed in non-FGR pups. Conclusion This study demonstrated that in both FGR and non-FGR neonates, a range of adaptive neurodevelopmental processes takes place, which may result in altered cellular morphology, chronic stress, poor memory and learning outcomes. Furthermore, this study highlighted that not only FGR, but also appropriately grown pups, which have been exposed to prenatal food deprivation may be at increased risk for impaired cognitive and developmental outcomes.